Bibliometric Studies in CIMEL: A Latin-American Medical Student Journal and the Future of Bibliometric Publications - Francisco J. Bonilla-Escobar; Johanna C. Rojas-Mírquez; Alvaro Mondragón-Cardona; Juliana Bonilla-Velez (University Library System, University of Pittsburgh, 2013)
Background: Bibliometric or scientometric studies are methodological fields focused on the structural analysis of the information contained in scientific publication and generate indicators that help identify challenges and achievements in research. We aimed to characterize the publications that used this method authored by medical students in Latin America.  Methods: We reviewed articles that performed a bibliometric analysis and were published in a Latin American medical student journal, between 2001 and 2012. We analyzed the characteristics of the articles, authors and references. Linear simple regression and Pearson correlation coefficient (PCC) were developed to identify trends and correlations with 95% confidence.  Results: There were 12 volumes of the journal available online, with a total of 236 articles. Of these, 13 (5.5%) were bibliometric studies: five original articles, four letters to the editor, two editorials, one short communication, and one review. There was a positive significant relationship between time (years) and number of publications (ß1=0.16, p=0.03, PCC=63%), and citations of each article (not significant, ß1=1.3, p=0.09, PCC=49%).  Conclusion: There was an increase in the number of bibliometric publications after 2008, possibly influenced by a popularization of these types of studies in Latin America. Findings should motivate new and collaborative studies in this field. Moreover, it will be necessary to clarify publication areas of interest of medical students around the world.